Optimal hybrid precoder design for millimeter-wave massive MIMO systems. (April 2022) - Kabalci, Yasin; Ahmadi, Mustafa; Ali, Muhammad
Abstract: Millimeter-waves (mmWave) have emerged as a promising candidate for next-generation communication systems. However, they have severe degradation issues that can be overcome by multiple-input multiple-output (MIMO) technology. Still, high-power consumption and budget issues are associated with multiple antennas. Therefore, hybrid precoders are exploited to combat these inevitable issues. The prime objective of this manuscript is to develop a hybrid precoder for massive MIMO systems that can provide better performance than the existing ones in terms of bit error rate (BER) versus signal-to-noise ratio (SNR). In this context, we exploit iterative geometric mean decomposition (IGMD) method that presents asymptotically optimum performance not only in traditional MIMO systems but also in massive MIMO systems. Later, the outcomes of the proposed scheme are compared with a recent design exploiting generalized triangular decomposition (GTD) scheme. The simulation studies show that the proposed method provides more than 7 dB improvement according to other designs. Highlights: This paper presents a novel hybrid precoder design for mmWave massive MIMO systems. Extensive performance analyzes are conducted to validate the proposed design. The designed system provides better results than that of the other available designs. The proposed system can be efficiently utilized in mmWave massive MIMO systems.